Encapsulation of CO2 into amorphous and crystalline α-cyclodextrin powders and the characterization of the complexes formed. (15th November 2015) - Ho, Thao M.; Howes, Tony; Bhandari, Bhesh R.
Highlights: CO2 complexation was undertaken into amorphous and crystalline α-CD solid matrices. Inclusion complexes were characterized by SEM, FTIR, NMR, X-ray, DSC and TGA. Amorphous α-CD entrapped more CO2 than crystalline at low pressure and short time. Complex formation was confirmed by appearing of a CO2 peak on FTIR and NMR spectra. Abstract: Carbon dioxide complexation was undertaken into solid matrices of amorphous and crystalline α-cyclodextrin (α-CD) powders, under various pressures (0.4–1.6 MPa) and time periods (4–96 h). The results show that the encapsulation capacity of crystalline α-CD was significantly lower than that of amorphous α-CD at low pressure and short time (0.4–0.8 MPa and 4–24 h), but was markedly enhanced with an increase of pressure and prolongation of encapsulation time. For each pressure level tested, the time required to reach a near equilibrium encapsulation capacity of the crystalline powder was around 48 h, which was much longer than that of the amorphous one, which only required about 8 h. The inclusion complex formation of both types of α-CD powders was confirmed by the appearance of a CO2 peak on the FTIR and NMR spectra. Moreover, inclusion complexes were also characterized by DSC, TGA, SEM and X-ray analyses.